2023
DOI: 10.3390/nu15143147
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Fiber Intake and Serum Klotho Levels in Americans: A Cross-Sectional Study from the National Health and Nutrition Examination Survey

Abstract: Background: Klotho is an aging-related marker closely associated with a number of diseases. A growing body of evidence suggests that dietary factors and lifestyle habits can impact serum Klotho levels. The effect of dietary fiber, a key component of a healthy diet, on the body’s serum Klotho levels has not been fully elucidated. Objective: The aim of this study was to explore the relationship between dietary fiber intake and serum Klotho levels in people aged 40–79 years in the United States. Methods: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…A study showed a positive correlation between total carotenoid intake and plasma S-Klotho levels in the elderly 26 . Also, a previous study showed that dietary ber intake was positively correlated with serum Klotho protein levels 27 . The above conclusions were consistent with our results, that is, the higher the dietary OBS, the higher the concentration of serum Klotho.…”
Section: Discussionmentioning
confidence: 95%
“…A study showed a positive correlation between total carotenoid intake and plasma S-Klotho levels in the elderly 26 . Also, a previous study showed that dietary ber intake was positively correlated with serum Klotho protein levels 27 . The above conclusions were consistent with our results, that is, the higher the dietary OBS, the higher the concentration of serum Klotho.…”
Section: Discussionmentioning
confidence: 95%
“…Current therapeutic approaches to enhance klotho expression include the administration of recombinant klotho protein (48). Additionally, strategies involving the supplementation of potential nutrients that boost endogenous klotho production, such as vitamin D (49), and increased dietary fiber intake (50) Dose-response relationship between klotho and low muscle mass. Values represent difference in predicted response in reference to a klotho of mean.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that several mechanisms may underlie these observed relationships. Dietary carbohydrates themselves can serve as a source of certain vitamins [ 33 , 34 ], minerals [ 35 ], and fiber [ 27 ], which could positively influence Klotho protein expression. Additionally, low-carbohydrate-intake diets tend to inevitably reduce the intake of high-quality carbohydrates [ 28 , 36 ], including fruits, non-starchy vegetables, and whole grains, and simultaneously alter the amount and type of gut microbiota and affect hepatic FGF21 production [ 20 , 37 ], all of which may downregulate Klotho levels by modulating the levels of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The following potential covariates associated with serum Klotho levels based on previous research were considered [ 25 , 26 , 27 , 28 ], including age (in continuous), gender (male/female), race (non-Hispanic White/non-Hispanic Black/other Hispanic and Mexican American/other), educational level (<high school/high school/college or above), and income-to-poverty ratio (PIR) obtained from demographic data. Serum cotinine levels (with a serum cotinine cutoff value of 3 ng/mL used to determine smoking status), along with information on alcohol consumption (classified as fewer than 12 drinks per year or more than 12 drinks per year), weight, and height were collected from data obtained at mobile examination centers.…”
Section: Methodsmentioning
confidence: 99%